Defining social content and social content management: Service science perspective - Wan Azlin Zurita Wan Ahmad; Muriati Mukhtar; Yazrina Yahya (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
Social media enables unlimited open interactions between organisations and customers. Social content resulting from social media interactions are of immense value and could be beneficial to both organisations and customers. Well managed social content could be used as a basis for producing service innovations offered by the organisations. However, the meaning of social content and its definition is not clearly articulated in the literature. This led to an equally limited meaning of social content management. In this regard, this article proposed that the definition of social content and social content management should be developed from the service science perspective. This is necessary to capture the essential facet of social interactions, that of value co-creation. Both definitions are developed through a triangulation process namely, literature review and a series of interviews with experts. With the proposed definition of social content and social content management, it is hoped that it would enhance the understanding of both concepts thus leading to a more effective way of managing social content.